Improving the storage quality and suppressing off-flavor generation of winter jujube by precise micro-perforated MAP - Cui, Xinzhi; Ding, Yibing; Sun, Chanchan; Li, Xiulian; Yuan, Shuzhi; Guo, Fengjun; Zeng, Xiangquan; Fan, Xinguang; Sun, Shuyang (Frontiers in Plant Science, 2024)
Using the Del-Valle model and Fick's law, we optimized microporous film parameters for winter jujube based on respiration rate, storage temperature, and gas composition. We evaluated the storage quality of winter jujube in PMP-MAP (precise micro-perforated modified atmosphere packaging), NP-MAP (non-perforated modified atmosphere packaging), and MP-MAP (macro-perforated modified atmosphere packaging) at 20 o C and 2 o C. PMP-MAP effectively inhibited respiration rate, maintained TSS and TA levels, and reduced decay rate of winter jujube. The PMP-MAP remained the antioxidant capacities at relatively higher levels, maintained the flavor, inhibited the occurrence of winter jujube alcoholism and the emergence of off-flavors, which could be explained that PMP-MAP could provide effective gas exchange, expelling excess CO2 and replenishing O2, which prevented anaerobic stress and quality degradation. Therefore, this approach for PMP-MAP is an efficient method for storage of winter jujube.